Feasibility Study of The Serabi Co.: Opportunities and Challenges in Jababeka Cikarang Clean Market - Ramadhan, Gilang; Nur’aini, Niken Paramitha; Aini, Regia Hurul; Putri, Sesilia Nadila Eka; Prayoga, Yohanes (Lentera Ilmu Nusantara, 2025)
This study examines the business opportunities and challenges of The Serabi Co. in the Jababeka Clean Market in Cikarang through a comprehensive feasibility study. Using a mixed method, the study combines a qualitative approach to analyze marketing, human resources, and operational aspects, and a quantitative approach to assess financial feasibility. Data collection was conducted through interviews, observations, questionnaires, and literature studies. The results show that The Serabi Co. has positive prospects with a strategic location in an industrial area and a growing trend of interest in traditional culinary delights with modern innovations. The main challenges include intense competition in the culinary market, fluctuations in raw material prices, and the need for consistent product quality. The business feasibility analysis shows that The Serabi Co. has the potential to become a popular culinary choice in the Jababeka Clean Market with proper management.